Copyright Infringement in the Market for Digital Images - Luo, Hong; Mortimer, Julie Holland (American Economic Review, 2016)
Digital technologies for sharing creative goods create new opportunities for copyright infringement and challenge established enforcement methods. We establish several important facts about the nature of copyright infringement and efforts to settle past infringing use in the market for digital images. Infringement in this, and many other markets, is often uninformed: users may be unaware that their use infringes, and may lack information about the price of a license. The uninformed nature of infringement implies that price may not be the primary factor in the decision to settle past use; in contrast, non-price factors may significantly affect settlement outcomes.